Sibling Rivalry in Jeff Kinney’s Diary of a Wimpy Kid: Rodrick Rules (2008) - Desiree Della (Passage, 2019)
This study investigates the portrayal of sibling rivalry in the novel Diary of a Wimpy Kid: Rodrick Rules (2008) by Jeff Kinney. The purpose of this study is to describe how sibling rivalry is portrayed in the novel Diary of a Wimpy Kid: Rodrick Rules. The sibling rivalry aspects in the novel is analyzed using the theory of psychoanalysis proposed by Freud (1989) through the events occurring in the novel among the Heffley siblings, which are Rodrick, Greg, and Manny. This study is also supported by the theory of sibling rivalry proposed by Hurlock (2001). This study uses a qualitative method to interpret the data. From the analysis of the study, it was found that the sibling rivalry aspects portrayed in the novel appear in the Heffley sibling’s id, ego, and superego. The findings of the study suggest that the novel portrays some of the sibling rivalry aspects proposed by Hurlock (2001), which are aggression and jealousy. The portrayal of sibling rivalry in the novel is articulated through selfishness, aggression, competition, humiliation, avoidance, jealousy, and lack of appreciation. In addition, the most dominant sibling rivalry aspect is selfishness. However, the sibling rivalry aspects between the Heffley sibling is different from one to another; the eldest, Rodrick, shows the most sibling rivalry aspects. Keywords: ego, id, psychoanalysis, sibling rivalry, superego